Visual Schema Displacement Therapy versus Eye Movement Desensitization and Reprocessing therapy versus waitlist in the treatment of post-traumatic stress disorder: results of a randomized clinical trial - Matthijssen, Suzy J. M. A.; Brouwers, Thomas C.; de Jongh, Ad (Frontiers in Psychiatry, 2024)
Introduction. Visual Schema Displacement Therapy (VSDT) is a novel approach showing promise in mitigating distressing memories, akin to Eye Movement Desensitization and Reprocessing (EMDR). Objectives. This study aimed to determine the safety, feasibility, and effectiveness of VSDT in individuals with post-traumatic stress disorder (PTSD), comparing it to EMDR therapy and a waitlist control condition (WLCC). It was hypothesized that the application of VSDT would be safe and PTSD symptoms significantly be reduced from both baseline to post-treatment and from baseline to follow-up in the VSDT and EMDR therapy conditions. Furthermore, we expected both treatments to be significantly more effective than the waitlist control. Moreover, we hypothesized that VSDT and EMDR therapy would be associated with significant improvements in symptoms of depression and general psychopathology. Method. Forty-six adults with PTSD were randomly assigned to VSDT, EMDR therapy, or WLCC, receiving six 90-minute sessions. Assessments included the Clinician Administered PTSD Scale for the Diagnostic Statistical Manual (DSM) -5 (CAPS-5), PTSD Checklist for DSM-5 (PCL-5), Beck Depression Inventory-II (BDI-II) and Brief Symptom Inventory (BSI) before, during, and 3 months post-treatment. Results. Bayesian analysis found no differences between VSDT and EMDR in PTSD symptom reduction but both outperformed WLCC. EMDR was superior to the WLCC in reducing symptoms of depression and general psychopathology. At 3-month follow-up, 58.3% of the participants in the VSDT condition no longer met the PTSD diagnostic criteria (41.2% EMDR therapy and 15.4% WLCC) with no difference between the two therapy conditions. Self-reported PTSD symptom reduction was significant in VSDT (d = 1.38) and EMDR (d = 1.40) but modest in WLCC (d = 0.39). Dropout rate was 19.3%, with no adverse events. Conclusion. This study supports VSDT's efficacy in treating PTSD, offering a valuable therapeutic option comparable to EMDR, with significant reductions in PTSD symptoms and but no difference with EMDR or the control condition for depressive symptoms and general psychopathology, and no reported adverse events.